Pedagogical work in professional education: From the denial of pedagogical to critical pedagogical work (Revista Contexto & Educação, 2026)
The article examines the challenges faced by pedagogues in Professional and Technological Education (PTE), especially within Federal Institutes. Based on literature review and one author’s professional experience, it highlights the growing presence of pedagogues in PTE - still underrepresented in teacher education programs. Key obstacles include the absence of PTE in initial training, undervaluing of pedagogical work, lack of institutional recognition, and struggles to assert a Critical Pedagogical Practice (CPP). Acting as educators or technicians, pedagogues play a vital role in fostering critical, emancipatory education for the working class. However, they face professional identity issues, limited support, and institutional misunderstanding of their roles. A review of CAPES theses and dissertations reveals a lack of research focused on pedagogical work in PTE. The article concludes that it is urgent to integrate PTE into pedagogy curricula, promote ongoing training, and value these professionals. Strengthening their role is key to enabling transformative and inclusive educational practices that support student retention, success, and emancipation.
Keywords: Pedagogy; Professional and Technological Education; Pedagogical Work